Palliative care in COVID-19 - Salas-Alarcón, Ibis Karina (2022)
Palliative care is presented as a strategy that improves the quality of life of the patient-family nucleus that are facing situations that put their lives at risk and the COVID-19 pandemic as a health emergency, has created the exact context, due to the extreme situation of great morbidity and mortality with great psychosocial and economic impact on the population, health staff and health systems, for the implementation of palliative care as a COVID care strategy.